Court cleaning behavior of the white-bearded manakin (manacus manacus) and a test of the anti-predation hypothesis - Cestari, Cesar [UNESP]; Pizo, Marco Aurelio [UNESP] (Wilson Ornithological Soc, 2014)
The cleaning of display courts is used by several forest lekking birds to possibly serve as an anti-predation strategy against terrestrial predators. Using a pit viper replica in the leaf litter 10-20 cm from the court (camouflaged predator) and in the central cleared area of the court (non-camouflaged predator) of the White-bearded Manakin Manacus inanacus we tested experimentally the anti-predation hypothesis. We also described the phenology of court cleaning by lekking males, and tested the relationship between court cleaning and the frequencies of display bouts by males, visits to courts by females, and the amount of debris falling on courts. Results showed that court cleaning had a defensive role against terrestrial predators, optimizing the time of detection of potential terrestrial predators in the cleared courts. Court cleaning was positively correlated with court visits by females, which may be related to the improvement of a male's plumage conspicuousness by enhancing the plumage contrast against the cleared court, as already demonstrated for M. vitellinus. If this is the case, then court cleaning may serve a dual role, as an anti-predation strategy and to enhance sexual exhibition by lekking males.
Keywords: Atlantic forest; lek; manakins; plumage conspicuousness